Artificial Intelligence and Canva-assisted Modeling the Way Methods to Improve the Multi-Representation Ability of Islamic Education Students - Arifa, Laily Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3129, 2024)
This study investigates applying the 'Modeling the Way' method, enhanced by artificial intelligence (AI) and Canva, to improve the multi-representation skills of students in the Islamic Education Studies Program (PAI) at Maulana Malik Ibrahim Malang UIN. Generation Z has unique learning characteristics and requires a more visual and interactive approach to education. This method uses AI to personalize learning experiences and Canva to facilitate the visualization of complex concepts. The study used an experimental design with a quantitative approach through pre-tests and post-tests to measure the verbal, mathematical, graphical, and symbolic representation skills of 58 students. The results showed a significant improvement in student multi-representation skills after the intervention, with an average increase of 31 points, from 49.75 in pre-tests to 80.75 in post-tests. Inferential statistical analysis suggests that this method has a significant positive impact on student abilities, marking the effectiveness of this innovative approach in meeting the learning needs of Generation Z. This research contributes to the literature by showing that integrating AI and Canva in learning can create a more dynamic and adaptive learning environment, improving student motivation and academic outcomes. These findings significantly impact the development of curricula and more effective teaching methods in higher education. This research suggests the need for additional experiments to test the effectiveness of these methods in different educational contexts, as well as the potential integration of other technological tools to enhance the learning experience. The use of AI and Canva as learning aids underlines the importance of adopting modern technology in education, improving academic achievement, and preparing students to face the challenges of the ever-expanding digital world.